PENDIDIKAN MORAL ANAK MELALUI PENGAJARAN BIDANG STUDI PPKn DAN PENDIDIKAN AGAMA - Fatimah Ibda (Jurnal Ilmiah Didaktika, 2012)
Moral education covers some approaches and methods to instruct the students with knowledge, attitudes, beliefs, skills and good moral behavior such as good, fair, concern to others and so on. The purpose of moral education is to produce individuals to be able to know personalities values and having moral commitment upon moral consistent values.